4CPS-230 Tailored medicines to optimise medicines administration to the older patient. (March 2019) - Hosford, J; Lynch, D; Sahm, L
Abstract : Background: Older patients (>65 years) present with a higher prevalence of dysphagia. This greatly complicates the administration of medicines to this group. To overcome this, nurses create 'tailored medicines' i.e. crushing tablets or opening capsules. However, such solid oral dosage form (SODF) manipulations may affect the safety or stability of medications. Clinical pharmacists have an important role in advising nurses to achieve optimal SODF administration to older dysphagic patients. Purpose: Establish whether SODF manipulations performed by nurses caring for older dysphagic patients comply with best practice guidelines. 1 2 Investigate nurses' experience of SODF manipulation and their views on the role of education in achieving optimal SODF administration. Material and methods: This study took place in a tertiary referral acute urban hospital with 850 beds over an 8 week period (February to March 2015) in a 35-bed care of the elderly ward. Patients were included in the study if they were >65 years and defined as having dysphagia if: receiving a modified consistency diet; nil by mouth; or receiving nasogastric or percutaneous endoscopic gastrostomy feeding. SODF manipulations were audited for compliance with best practice guidelines. 1 2 A questionnaire investigating nurses' experiences of SODF manipulation and what role pharmacists can play in advising them to achieve optimal practice in this area was developed. Data were analysed using Microsoft Excel. Ethical approval was granted by the Clinical Research and Ethics Committee of the Teaching Hospitals and the Quality Unit of the University Hospital. Results: Of 158 patients, 33 patients (>65 years and dysphagic) received one or more manipulated SODF. Of the 290 manipulations; 59.3% did not comply with best practice guidelines. Of the 18 nurses who completed the survey; 10 reported not having received training in SODF manipulation and 14 requested education on SODF manipulation. Sixteen nurses identified pharmacists as the most knowledgeable healthcare professional to deliver education on SODF manipulation. Conclusion: Inappropriate SODF manipulation is common practice in the care of the older patient with dysphagia. This study highlighted that pharmacists have been identified by nurses as playing a key role in ensuring that dysphagic patients receive safe, effective and appropriate medical treatment. References and/or acknowledgements: 1. https://www.pharmpress.com/product/9780857111623/handbook-of-drug-administration-via-enteral-feeding-tubes 2. http://www.newtguidelines.com/ No conflict of interest.